Teaching soft skills in higher education through serious games: validation of the Compete! gamification - Aida López-Serrano; Nadia McGowan; Pablo Moreno-Ger; Daniel Burgos (Smart Learning Environments)
Abstract Soft skills, essential for employability and professional success, are often underemphasised in traditional higher education curricula. This study assesses the effectiveness of Compete!, a serious game developed under the Erasmus+ program, in enhancing students' awareness of key soft skills, including creative problem-solving, effective communication, stress management, and teamwork. The game simulates professional scenarios requiring strategic decision-making, providing real-time feedback, and fostering reflective learning. A pilot test conducted with 63 business students at Universidad Internacional de La Rioja during the 2023–2024 academic year employed pre- and post-game surveys to assess changes in perceptions of soft skills. Results revealed statistically significant improvements across 13 of 18 competencies, with notable increases in confidence and the perceived importance of teamwork and stress management. Findings highlight the potential of serious games as innovative tools for integrating soft skills into higher education, underscoring their role in preparing students for the complex challenges of the workplace. The study calls for broader institutional adoption and curriculum integration of gamified approaches to enhance employability.